Significant activity: the motor chest, when movement is the treasure - Corso Amado, Camilo Ernesto
Regular practice of physical activity (PA) has demonstrated to bring multiple health benefits while staying sedentary for a long time has deleterious effects on the body. In Colombia, the 2015 National Survey of Nutritional Situation, allowed to evidence through the indicators to show that only about half of young people and adults (18 - 65 years) follow and fulfill the international PA recommendations. However, nationwide, there is no data related to the physical activity levels in the population with cognitive disabilities, in contrast, to the international data which results show that their participation is much lower compared to the general population. Therefore, it is necessary to identify cost-effective strategies that may increase PA levels in this population.